Expert System Diagnoses Android Handphone Damage Using Web-Based Dempster Shafer Method - Arianta Bangun; Achmad Fauzi; Rusmin Saragih (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Mobile is a communication tool that can be carried anywhere because it does not use cables like conventional fixed line telephones. Mobile phones can be obtained at very affordable prices so that mobile phones are no longer categorized as luxury goods. By using a mobile phone, users can make and receive calls to and from other mobile phone networks around the world. The sophisticated use of mobile phones can solve all interests more effectively and efficiently. Another function of mobile phones is that it can be a medium of entertainment, educational media, business media and so on. In general, every electronic item can be damaged and mobile phones are one of them. For example, it gets hot quickly, the battery runs low quickly and even the cellphone is in a condition that it can't turn on at all (totally dead). Damage that occurs can be categorized as light or heavy damage. So by knowing what category of damage occurs, it can make repairs or services on cellphones more optimal. To find out the damage that occurs requires a system that can categorize the damage to the android phone by using an expert system. An expert system is a system that can store the knowledge of experts or experts in the system. Expert systems are used to solve problems and improve problem solving abilities. Dempster Shafer is one method that can be used in expert systems. The Dempster Shafer method is a method of uncertainty to produce an accurate diagnosis. Due to the addition or deletion of new facts in the form of information about symptoms and disorders. This method gives experts confidence in their knowledge. So that from the case study conducted, it will be found that the Dempster Shafer method testing with the customer diagnoses based on the symptoms with a final value of 100%, the customer experiences Short Damage.